Social Capital, Entrepreneurial Leadership and SMEs Performance: The Mediating Effect of Innovation Capability - Astri Ayu Purwati; Budiyanto Budiyanto; Suhermin Suhermin (Universitas Negeri Malang, 2021)
This study aims to solve the problems of SMEs’ performance in the culinary and hospitality sectors in Pekanbaru by involving several companies’ internal environmental factors to build a competitive strategy. The variables engaged in this study consisted of social capital, entrepreneurial leadership, innovation capability, and performance. It involves 200 SMEs consisting of 167 culinary enterprises and 33 hospitality enterprises in Pekanbaru City in Riau of Indonesia. Using the structural equation model (SEM) approach, the results show that social capital has no significant direct effect on the business performance of culinary and hospitality SMEs in Pekanbaru. However, social capital indirectly affects SMEs’ performance through innovation capability. In addition, entrepreneurial leadership, directly and indirectly, affects the financial and non-financial performance of SMEs through capability. Culinary and hospitality SMEs in Pekanbaru must do a job in relationships partnerships with withs with common goals in furthering SMEs business. This active participation helps SMEs nurture knowledge and the latest information in the business world. Furthermore, culinary and hospitality SMEs actors were dominated by young entrepreneurs. It could be a valuable capital for SME act to be more innovative and creative in company improvement strategies, especially in coping with the COVID-19 pandemic. Keywords: Social capital, Entrepreneurial leadership, Innovation capability, SMEs performance